Fiber interferometer for hybrid optical and optoacoustic intravital microscopy - Shnaiderman, Rami; Wissmeyer, Georg; Seeger, Markus; Soliman, Dominik; Estrada, Hector; Razansky, Daniel; Rosenthal, Amir; Ntziachristos, Vasilis (Optica, 2017)
The addition of optoacoustic sensing to optical microscopy may supplement fluorescence contrast with label-free measurements of optical absorption, enhancing biological observation. However, the physical dimensions of many optoacoustic systems have restricted the implementation of hybrid optical and optoacoustic (O2A) microscopy to imaging thin samples in transmission mode or to ex-vivo investigations. Here we describe a miniaturized optoacoustic sensor, based on a π-phase-shifted fiber Bragg grating embedded in an acoustic cavity, which is virtually invisible to the optical path and can be seamlessly integrated into any conventional optical microscope. The new sensor enables, for the first time to our knowledge, entirely optical O2A intravital microscopy in epi-illumination mode, demonstrated by label-free optoacoustic and second-harmonic generation images of a mouse abdomen and ear. Our technique greatly simplifies the integration of acoustic detection in standard microscopes and could therefore make optoacoustic microscopy more accessible to the biomedical community.
CRIS-Team Scopus Importer:2023-03-08